Pengaruh Intellectual Capital Terhadap Financial Distress - Noviani Noviani; Nor Norisanti; Erry Sunarya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Retail sector in Indonesia is currently suffering a decrease like the lowering of revenue and the closing of their outlets. This research aims to determine the effect of Human Capital Efficiency, Structural Capital Efficiency and Capital Employed Efficiency on Financial Distress. The population in this study are the companies listed on Indonesia Stock Exchange the retail trade at 2020. The sample in this study are 23 companies which is the result of purposive sampling technique. The analytical technique used in this study is multiple linear regression analysis. The results of this study are (1) Human Capital Efficiency has a negative and significant effect on Financial Distress (2) Structural Capital Efficiency has a negative and significant effect on Financial Distress (3) Capital Employed Efficiency has a positive and significant effect on Financial Distress and (4) Human Capital Efficiency, Structural Capital Efficiency and Capital Employed Efficiency simultaneously has a significant effect on Financial Distress. Keywords : Human Capital Efficiency, Structural Capital Efficiency, Capital Employed Efficiency, Financial Distress